Hosoya polynomial of the subdivided join - Eunice Gogo Mphako-Banda; Thokozani Ncambalala (Kuwait Journal of Science)
The Hosoya polynomials of diameter 1 and diameter 2 graphs are known. We extend the concept of  a vertex join of a graph to q-vertex join. Then we give the formula of the Hosoya polynomial of a $q$-vertex join of a complete graph and the formula of the Hosoya polynomial of a q-vertex join of a diameter 2 graph.